ChemInform Abstract: An Eco‐Compatible Synthesis of Medicinally Important Novel Class of Trispiroheterocyclic Framework Using 2, 2, 2‐Trifluoroethanol as a Reusable Medium. Issue 18 (17th April 2014) - Dandia, Anshu; Singh, Ruby; Joshi, Jyoti; Kumari, Sukhbeer
Abstract 11 Trispirocompounds of type (IV) and (VI) are prepared and screened for their antifungal and antimycobacterial activities.